Arabic Learning Media Design Based on the MIT App Inventor Application - Rini; Hazuar; Shanti Novita (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
One of the supports for effective communication is the use of learning media. However, currently we don't find many interactive Arabic language learning media that are developed from computer programs and especially those based on Android which we usually know as Android Based Learning (ABL).This article aims to develop mobile learning-based learning media, namely interactive application based learning media. This learning media facilitates students to improve Arabic learning outcomes, and can produce interesting learning and can increase students' learning motivation. The results of this study after going through the assessment of the material aspect validator and the media aspect validator concluded that learning media designed based on Android using the MIP App Inventor application are suitable for use as alternative media for learning Arabic.